Inventarisasi Tumbuhan yang Berpotensi Penghasil Minyak Atsiri dari Famili Lamiaceae di Sumatera Barat Berbasis Spesimen Herbarium - Ratih Wulandari; Nurainas Nurainas; Aadrean Aadrean; Syamsuardi Syamsuardi; Retno Prihatini (Jurnal Biologi Universitas Andalas, 2023)
Lamiaceae is an important plant family that inhabits various ecosystems and has great diversity, is considered a cosmopolitan plant and has an important role in pharmaceutical and cosmetic sciences because of its essential oil content in almost every species. This research was focused on identify plant species from the Lamiacecae family that potential as essential oil producer in West Sumatra with their distribution based on ANDA Herbarium specimens. Data was collected use the herbarium method and literature study to determine the potential of each species. The results showed in the ANDA Herbarium were 45 species from 20 genera, which dominated by species that have the potential to produce essential oils as many as 23 species, followed by species that had not explore for their essential oil content as 11 species and commercial species,  9 species. Species from most Lamiaceae family were potentially as essential oil producer found in Padang city administrative area. Keywords: Cosmopolitan, genera, commercial, distribution, potential